014 Medical student and consultant surveys assessing educational value of telephone and video neurology clinics. Issue 9 (12th August 2022) - Balfour, Katharine; Lavin, Tim
Abstract : Introduction: The COVID-19 pandemic affected medical students experience of clinical neurology. Outpatient clinics reverted to telephone or video consultations. We sought to assess the impact of this change via a survey of both students and consultant neurologists. Methods: An online 14-part questionnaire using Likert scales and free text options was distributed to all Year 4 medical students and consultant neurologists via email. Results: 366 students received the survey and 39 responded (an 11% response rate). 41 consultants received the survey and 9 responded (a 22% response rate). 83% of consultants felt the student's inter- action with the patient was affected by the telephone/video software. 29% of students strongly agreed and 36% agreed that technological barriers impacted their learning experience. The free text student feedback highlighted good practice. We developed best practice guidance which included use of video consultation software, student engagement and clinic debrief. This was distributed as digestible checklists for students and clinicians. The limitations of this survey are the small response rates of both consultant and student groups. Conclusion: Remote consultations are likely to remain part of neurological practice. Ongoing evaluation of its effect on medical student education and specific guidance for educators is required.